Perlakuan Akuntansi atas Biaya Lingkungan pada RS Perkebunan dan RSUD Balung di Kabupaten Jember: Pendekatan Observasional - Cici Megananda (Universitas Jember, 2019)
This research aims to know the accounting treatment of environmental costs at RS Perkebunan and RSUD Balung, to measure the level of deffrence or similarity both hospitals and to measure the level of compliance with Accounting Standards and applicable accounting concepts. This research is descriptive research with qualitative approach, a method is done by collecting, preparing and analyzing descriptive data obtained through observation, interviews, documentation and comparison of the data both hospitals. To minimize errors thay may occur, this research used data triangulation. The results showed some differences and similarities in the accounting treatment of environmental costs carried by RS Perkebunan and RSUD Balung in Jember. Differences arise because the two hospitals have a difference in the application of standards and policy management so that the level of compliance based on the accounting standards applied. Keywords: accounting, environmental, waste, hospital